1997
DOI: 10.1104/pp.113.2.511
|View full text |Cite
|
Sign up to set email alerts
|

Pyrophosphorylases in Potato (V. Allelic Polymorphism of UDP-Glucose Pyrophosphorylase in Potato Cultivars and Its Association with Tuber Resistance to Sweetening in the Cold)

Abstract: The two alleles, designated ugpA and ugpB, were identified by the absence and presence of a BamHl site, respectively. The relative band intensities of the two cDNA populations following polymerase chain reaction amplification and agarose gel electrophoresis were related to a potato cultivar's ability to resist sweetening when exposed to cold temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(21 citation statements)
references
References 17 publications
0
19
0
1
Order By: Relevance
“…The cultivars (Snowden and Russet Burbank) and selection (ND860-2), that exhibit a degree of resistance to CIS, contain primarily the UgpA allele. Both types of alleles have been cloned from Russet Burbank which has been shown to be triplex and simplex for the alleles UgpA and UgpB, respectively (Sowokinos et al, 1997). The catalytic properties of the UGPase polypeptides encoded by the different allelic types (i.e., plus or minus a BamH1 site) as they may relate to the regulation of CIS, has also been discussed previously (Gupta and Sowokinos, 2003).…”
Section: Article In Pressmentioning
confidence: 97%
See 2 more Smart Citations
“…The cultivars (Snowden and Russet Burbank) and selection (ND860-2), that exhibit a degree of resistance to CIS, contain primarily the UgpA allele. Both types of alleles have been cloned from Russet Burbank which has been shown to be triplex and simplex for the alleles UgpA and UgpB, respectively (Sowokinos et al, 1997). The catalytic properties of the UGPase polypeptides encoded by the different allelic types (i.e., plus or minus a BamH1 site) as they may relate to the regulation of CIS, has also been discussed previously (Gupta and Sowokinos, 2003).…”
Section: Article In Pressmentioning
confidence: 97%
“…Counting from the A of the ATG start codon, a distinguishing feature among the new cDNAs described in this study was the presence or absence of this BamH1 site between bp positions 1315-1320. Previously we have presented evidence that cultivars that experience susceptibility to CIS possess a predominance of the UgpB allele containing the BamH1 site (Sowokinos et al, 1997). Cultivars that demonstrated a degree of resistance to CIS are quadruplex or triplex with respect to UgpA allele that lacks this BamH1 site (Sowokinos, 2001a).…”
Section: Article In Pressmentioning
confidence: 98%
See 1 more Smart Citation
“…Enzyme reactions directly involved in free sugar formation in potato cells are UDP-Glucose pyrophosphorylase (UGPase), sucrose 6-P synthase (SPS), sucrose 6-P phosphatase and acid invertase (Sowokinos et al 1997). Hill et al (1996) reported that following initiation of coldsweetening in potatoes the concentration of sucrose increased and decreased in parallel with the concentration of UDP-Glucose.…”
Section: Introductionmentioning
confidence: 99%
“…2) led to decreased hexoses and increases sucrose (Zrenner et al 1996). Allelic genotypes of UGPase in potato plants were reported to be different in potato clones that have different sensitivity to cold sweetening (Sowokinos et al 1997;Sowokinos 2001;Gupta and Sowokinos 2003). Most of the cold-resistant potatoes were unique in that they contained up to two UGPase isoforms that were slightly more basic in charge than the most common isoform in cold sweetening-sensitive cultivars (Sowokinos 2001).…”
Section: Cold Sweetening and Chip Color Molecular And Genomics Analysmentioning
confidence: 99%